A nonlocal softening plasticity based on microplane theory for concrete at finite strains. (December 2020) - Indriyantho, Bobby Rio; Zreid, Imadeddin; Kaliske, Michael
Highlights: A microplane plasticity approach is extended to the finite strain framework. Regularisation and mesh insensitivity are achieved by the implicit gradient enhanced method. Significant differences in plastic deformations between the small and finite strain models are observed. Abstract: Parts of the irreversible response of materials can be described by a plasticity approach. For modelling quasi-brittle materials such as concrete, the microplane approach is a powerful method. In order to predict the load–displacement as well as the stress–strain relation, numerous constitutive models developed for small strains have been used successfully. Nevertheless, for example, at high hydrostatic pressure, extremely large deformations occur even in concrete materials with no damage or voids. As consequence, the microplane-plasticity model at small strains needs to be extended to the finite strain framework for largely deformed structures. The elastoplastic microplane approach based on the kinematic constraint of the volumetric-deviatoric split and the Drucker-Prager yield criterion at finite strains are implemented in the present work. Furthermore, due to strain localisation, an implicit gradient enhanced approach is applied in here to obtain stable and mesh insensitive solutions. Numerical examples including the comparison of simulated results to existing experimental data are provided to validate the proposed formulation.